Curcumin as a Therapeutic Option in Retinal Diseases - Daniel López-Malo (Antioxidants, 2020)
The retina is subjected to oxidative stress due to its high vascularization, long time light exposition and a high density of mitochondria. Oxidative stress can lead to pathological processes, like cell apoptosis, angiogenesis and inflammation ending in retinal pathologies. Curcumin, a major bioactive component obtained from the spice turmeric (Curcuma longa) rhizome has been used for centuries in Asian countries for cooking and for curing all kinds of diseases like dysentery, chest congestion and pain in general, due to its antioxidant effects. Curcumin prevents the formation of reactive oxygen species and so it is a good protective agent. Curcumin has shown also anti-inflammatory, and antitumor properties. Curcumin is a natural product, which can be a therapeutic option in a variety of retinal diseases due to its pleiotropic properties. Some drawbacks are its poor solubility, bioavailability and lack of stability at physiological conditions; which have been shown in curcumin skeptical publications. In this review, we provide some lights and shadows on curcumin administration on the major retinal pathologies.